2021
DOI: 10.1093/noajnl/vdab188
|View full text |Cite
|
Sign up to set email alerts
|

Osimertinib in advanced EGFR-mutant lung adenocarcinoma with asymptomatic brain metastases: an open-label, 3-arm, phase II pilot study

Abstract: Background Osimertinib is selective for both EGFR-TKI sensitizing and Thr790Met mutations. While intracranial activity of osimertinib is documented in larger trials, a prospective study focusing exclusively on patients with asymptomatic brain metastases has not been reported. Methods In this nonrandomized, phase II, open label, 3-arm prospective proof-of-concept pilot study, 48 patients with metastatic EGFR-mutant lung adenoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Similarly, a subgroup analysis of the FLAURA study showed that compared with standard first-line EGFR-TKIs (gefitinib or erlotinib), osimertinib demonstrated a higher CNS ORR (91% versus 68%) and longer CNS PFS (not reached versus 13.9 months) in patients with CNS metastases [228]. Peled et al also reported that osimertinib displayed potent intracranial activity against EGFR-mutant lung adenocarcinoma with asymptomatic brain metastases in both previously treated and treatment-naive groups, regardless of T790M status [229]. Importantly, in addition to its effect on existing CNS metastases, osimertinib also plays a protective role in CNS progression.…”
Section: Management Of Cns Metastasesmentioning
confidence: 99%
“…Similarly, a subgroup analysis of the FLAURA study showed that compared with standard first-line EGFR-TKIs (gefitinib or erlotinib), osimertinib demonstrated a higher CNS ORR (91% versus 68%) and longer CNS PFS (not reached versus 13.9 months) in patients with CNS metastases [228]. Peled et al also reported that osimertinib displayed potent intracranial activity against EGFR-mutant lung adenocarcinoma with asymptomatic brain metastases in both previously treated and treatment-naive groups, regardless of T790M status [229]. Importantly, in addition to its effect on existing CNS metastases, osimertinib also plays a protective role in CNS progression.…”
Section: Management Of Cns Metastasesmentioning
confidence: 99%
“…Irreversible inhibitor of EGFR, osimertinib, has shown efficiency in crossing the blood-brain barrier (BBB) and significantly Potential Role of Cancer Stem Cells in Glioblastoma: A Therapeutic Aspect DOI: http://dx.doi.org/10.5772/intechopen.106332 inhibits GBM tumorigenesis in-vivo [114]. It has also entered phase II clinical studies [115][116], however, has shown to be marginally effective, which could be due to heterogeneity of GBM [117][118]. Further, combined treatment of antibodies against EGFRvIII and CD133 showed higher effectivity in elimination of GSCs compared with the antibody against either EGFRvIII or CD133 [111].…”
Section: Targeting Gsc Markers and Related Signaling Pathwaysmentioning
confidence: 99%
“…Third-generation EGFR TKIs, such as osimertinib, are also irreversible inhibitors, but show much more efficient blood–brain barrier (BBB) penetration than those from other generations due to its lower efflux by BBB multidrug efflux pumps, suggesting its potential use for treating brain cancer [ 94 , 95 ]. Several phase II clinical studies have shown that osimertinib can be used for treating EGFR-mutant lung adenocarcinoma with brain metastasis [ 96 , 97 ]. Osimertinib shows excellent BBB penetration and significantly inhibits GBM tumorigenesis in vivo [ 98 ].…”
Section: Strategies Targeting Gscsmentioning
confidence: 99%